Introduction: Cultural Production and Negotiation of Borders - Schimanski, Johan; Wolfe, Stephen Frank (Nordlit, 2009)
The essays in this issue of Nordlit focus on how historical and contemporary border discourses, expressive and aesthetic representations, are generated, circulated, and interpreted in both local and global contexts.